Literature Review: The Use of Professional Technology in the Integration of ESD (Education for Sustainable Development) in Social Science Learning - Wildan Fitroni; Yasinta Salsabilah Ramadani; Rendy Dwi Cahya; Mukhammad Rafly Eka Rosyadi; Noval Maleakhi Hulu (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to explore the potential of utilizing professional technology in integrating Education for Sustainable Development (ESD) into social science learning. Method: This study employs a literature review method with a descriptive qualitative approach to ten selected articles based on the research objectives. Analysis was conducted through the identification, categorization, and synthesis of findings related to the types of technology used, ESD integration strategies, and their impact on learning.  Results:  The results of the study indicate that technologies such as digital platforms, artificial intelligence, mobile learning, VR/AR, simulations, and game-based learning can enhance student engagement, motivation, conceptual understanding, critical thinking skills, collaboration, and intelligence regarding sustainable issues in social science learning. The effectiveness of technology integration is influenced by appropriate pedagogical design, teacher readiness, infrastructure support, and cultural and social context suitability. Novelty: This research's novelty lies in the comprehensive synthesis that maps the relationship between professional technology, active learning models, and ESD outcomes in social science learning, while also offering future research directions to address facility limitations, the digital divide, and the lack of teacher training.